Deformation Properties of Rubberized Engineered Cementitious Composites Using Response Surface Methodology - Mohammed, B.S. (Springer Science and Business Media Deutschland GmbH, 2021)
This study reports the effects of crumb rubber and polyvinyl alcohol fibre (PVA) on the deformation properties of rubberized engineered cementitious composites (R-ECCs), including drying shrinkage, elastic modulus, and Poissonâs ratio. By utilizing response surface methodology, two variables have been considered in developing R-ECC mixtures which are the amount of crumb rubber replacement to fine aggregate by volume 0â5 and PVA fibres from 0 to 2 by volume of cementitious materials. Experimental data show that the incorporation of crumb rubber into ECC results in decreasing its compressive strength and elastic modulus. A significant increase in Poissonâs ratio and drying shrinkage was reported with the incorporation of crumb rubber. DesignâExpert software has been utilized to construct predictive models for the responses. The goodness of fit between the measured and predicted values is validated using the coefficient of determination. Results of numerical optimizations showed that the best mixture was obtained by combining 1.92 of crumb rubber with 1.86 of PVA fibres. The optimization results of the prediction model were conducted to acquire the optimal solution variables. The variation obtained between the predicted results and the validation results is less than 5. Â© 2020, Shiraz University.